Paternal obesity initiates metabolic disturbances in two generations of mice with incomplete penetrance to the F2 generation and alters the transcriptional profile of testis and sperm microRNA content. Issue 10 (11th July 2013) - Fullston, Tod; Teague, E. Maria C. Ohlsson; Palmer, Nicole O.; DeBlasio, Miles J.; Mitchell, Megan; Corbett, Mark; Print, Cristin G.; Owens, Julie A.; Lane, Michelle
Abstract : Obesity is highly prevalent, and its incidence is increasing. The previous study showing a major effect of paternal obesity on metabolic health of offspring is confounded by comorbidity with diabetes. Therefore, we investigated the effect of diet‐induced paternal obesity, in the absence of diabetes, on the metabolic health of two resultant generations and the molecular profiles of the testes and sperm. Founder (F0 ) male C57BL6 mice were fed either a high‐fat diet (HFD) or a control diet (CD); n = 10/diet for a period of 10 wk. Testis expression of mRNA/microRNAs was analyzed by microarray and qPCR and sperm microRNA abundance by qPCR Two subsequent generations were generated by mating F0 and then F1 mice to CD mice, and their metabolic health was investigated. All mice, other than F0 males, were maintained on a CD. HFD feeding induced paternal obesity with a 21% increase in adiposity, but not overt diabetes, and initiated intergenerational transmission of obesity and insulin resistance in two generations of offspring. This distinct phenotypic constellation is either partially or fully transmitted to both female and male F1 offspring and further transmitted through both parental lineages to the F2 generation, with a heightened effect on female F1 offspring (+67% in adiposity) and their F2 sons (+24% in adiposity). Founder male obesity altered the testes expression of 414 mRNAs by microarray and 11 microRNAs by qPCR, concomitant with alterations in sperm microRNA content and a 25% reduction in global methylation of germ cell DNA Diet‐induced paternal obesity modulates sperm microRNA content and germ cell methylation status, which are potential signals that program offspring health and initiate the transmission of obesity and impaired metabolic health to future generations. This study implicates paternal obesity in the transgenerational amplification of obesity and type 2 diabetes in humans.—Fullston, T., Ohlsson Teague, E. M. C., Palmer, N. O., DeBlasio, M. J., Mitchell, M., Corbett, M., Print, C. G., Owens, J. A., Lane, M., Paternal obesity initiates metabolic disturbances in two generations of mice with incomplete penetrance to the F2 generation and alters the transcriptional profile of testis and sperm microRNA content. FASEBJ. 27, 4226‐4243 (2013). www.fasebj.org